Global burden of inflammatory bowel disease in children and adolescents, 1990–2021: trends, age-specific patterns and future projections - Tan, Hai-Qing; Li, Qian-Kun; Jiang, Mu-Rong; Bin, Dong-Hua (Frontiers in Pediatrics, 2025)
IntroductionRecent epidemiological trends have revealed a marked increase in incidence among children and adolescents. This study aimed to analyze the global burden of inflammatory bowel disease (IBD) among children and adolescents aged 0–19 years from 1990 to 2021 systematically, focusing on regional and age-specific trends and future projections, with the aim of informing global prevention and control strategies.MethodsData on IBD incidence, mortality, and disability-adjusted life years (DALYs) were obtained for 204 countries and territories from the Global Burden of Disease Study 2021 (GBD 2021). Temporal trends were evaluated via the estimated annual percentage change (EAPC) and average annual percentage change (AAPC). A Bayesian age-period-cohort (BAPC) model was used to project the disease burden through 2050. The relationship between the sociodemographic index (SDI) and disease burden was also assessed, with Spearman's rank correlation coefficient applied for correlation analysis.ResultsGlobally, the incidence of IBD among children and adolescents remained stable (EAPC = −0.03%, 95% CI: −0.44–0.38), although marked regional disparities were observed. The incidence rates were stable or declined in high-income countries (e.g., high-income North America: EAPC = −1.07, 95% CI: −1.82–−0.32), whereas industrializing regions showed significant increases (e.g., East Asia: EAPC = 2.01, 95% CI: 1.02–3.19). Although very early-onset IBD (VEO-IBD) is rare, it is associated with disproportionately high mortality and DALY rates based on indirect estimates derived from the <5-year-old group, which may have inherent limitations. Globally, mortality has decreased by 51.6% and DALYs by 49.5%, yet the burden remains high in low-SDI regions. Projections suggest that by 2050, the incidence may reach 0.71 per 100,000, while mortality and DALY rates will continue to decline.DiscussionThe global burden of IBD in children and adolescents is characterized by significant regional disparities, with VEO-IBD presenting unique challenges. Targeted interventions—including early diagnosis, enhanced multidisciplinary care, and international collaboration—are urgently needed, especially in low- and middle-income countries where resource allocation and disease management remain limited.